2004
DOI: 10.1021/bi035625z
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Processing of HIV-1 Nucleocapsid Protein by the Viral Proteinase:  Effects of Amino Acid Substitutions at the Scissile Bond in the Proximal Zinc Finger Sequence

Abstract: The human immunodeficiency virus type 1 (HIV-1) nucleocapsid protein flanked by Gag sequences (r-preNC) was expressed in Escherichia coli and purified. HIV-1 proteinase cleaved r-preNC to the "mature" NCp7 form, which is comprised of 55 residues. Further incubation resulted in cleavages of NCp7 itself between Phe16 and Asn17 of the proximal zinc finger domain and between Cys49 and Thr50 in the C-terminal part. Kinetic parameters determined for the cleavage of oligopeptides corresponding to the cleavage sites i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 57 publications
3
11
0
Order By: Relevance
“…NCp15 and NCp9 appear only transiently but their lifetime is specifically programmed (41). Additional cleavage sites within NCp7 have been proposed based on in vitro peptide cleavage experiments (42), but NCp15, NCp9 and NCp7 are the three major forms that have been observed by the numerous studies mentioned thus far on Gag and NC precursor cleavage processes. Although all three forms of NC have an overall positive charge (p I = 9.50–10.15), the C-terminal p6 domain of NCp15 contains eight acidic residues and has a p I of 4.50 (Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…NCp15 and NCp9 appear only transiently but their lifetime is specifically programmed (41). Additional cleavage sites within NCp7 have been proposed based on in vitro peptide cleavage experiments (42), but NCp15, NCp9 and NCp7 are the three major forms that have been observed by the numerous studies mentioned thus far on Gag and NC precursor cleavage processes. Although all three forms of NC have an overall positive charge (p I = 9.50–10.15), the C-terminal p6 domain of NCp15 contains eight acidic residues and has a p I of 4.50 (Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…Studies with chemically synthesized or recombinant proteins later also confirmed the shifted cleavage site [8,9]. Peptides representing the predicted cleavage sites in the second zinc-fingers were not substrates of the HIV-1 PR [8]; however, in vitro studies indicated another site of cleavage in the second zinc-finger [9]. Even though the cleavage within the retroviral NC zinc-fingers occurs in vitro in the presence of EDTA, labelled antibodies of the amino-and carboxyl-terminus of NC appeared to bind at different localizations in the nucleus of murine leukaemia virus-infected cells [10].…”
Section: Introductionmentioning
confidence: 84%
“…Based on the sequence homology with EIAV, originally, the oligopeptide substrate was predicted to be cleaved between Cys and Phe residues of the sequences representing the HIV-1 NC-1 cleavage site (KIVKCFNCGK) [6], but later, it was proved that the cleavage occurs one residue further from the expected place [7], between Phe and Asn residues (F16 and N17) of the first zinc-finger domain (Figure 1). Studies with chemically synthesized or recombinant proteins later also confirmed the shifted cleavage site [8,9]. Peptides representing the predicted cleavage sites in the second zinc-fingers were not substrates of the HIV-1 PR [8]; however, in vitro studies indicated another site of cleavage in the second zinc-finger [9].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In vitro experiment with the cores of another lentivirus; the equine infectious anemia virus, showed that the viral protease can cleave the nucleocapsid protein into smaller fragments leading to the suggestion of an early phase role for the PR. In previous studies it was established that proteins of the viral core (CA, NC) are substrates of the viral protease in vitro , while other studies identified over 30 cellular proteins that could be target of the PR as summarized in Wagner et al . .…”
mentioning
confidence: 99%